Process Evaluation of the Residential Substance Abuse Treatment Program at the Minnesota Department of Corrections, 1999 - Campbell, Todd C. ([Verlag nicht ermittelbar], 2003)
The objective of this process evaluation was to evaluate the integrity of the Minnesota Correctional Facility (MCF)-Red Wing Residential Substance Abuse Treatment (RSAT) program service delivery system in order to (1) provide feedback designed to enhance the existing strengths of the RSAT program and improve any existing or potential weaknesses, and (2) prepare for a subsequent outcome evaluation. The process evaluation data consist of two administrations of the Correctional Institution Environment Scale (CIES) (Parts 1 and 2) and three rounds of Rating of Facilitation of RSAT Groups (Parts 3-5). Resident-participants in this study were male juvenile offenders incarcerated at the MCF-Red Wing who had been determined to have significant substance abuse problems as an aspect of their delinquency. A total of 69 residents participated in the RSAT program during the course of the evaluation. All RSAT program residents were required to participate in all aspects of the program. Four caseworkers, one chemical dependency counselor, and two teachers participated in all aspects of the process evaluation. Ten corrections officers and three administrators participated in the CIES administration. There are four forms of the Correctional Institution Environment Scale (CIES): (1) The Real Form (Form R), (2) the Short Form (Form S), (3) the Ideal Form (Form I), and (4) the Expectations Form (Form E). Form R and Form I were employed in this study. Form R measures resident and staff perceptions of the current or "actual" climate of the program. Form I is worded to allow residents and staff to answer questions in terms of an ideal program. Both forms are comprised of 90 true-false statements. The CIES was administered twice for this study, with the first administration in September 1999. Participants in this administration of the CIES were 28 residents of the Princeton Cottage (the cottage that housed the RSAT participants) and 12 staff (administrators, caseworkers, and corrections officers). The second administration was in December 1999. Participants in this administration were 25 residents of the Princeton Cottage and 10 staff (administrators, caseworkers, and corrections officers). The surveys were collected and sent to Marquette University investigators for scoring and interpretation. An extensive evaluation of group facilitation was undertaken, with all groups videotaped between May 1999 and September 1999. These videotapes were shipped to Marquette University for review. In total, 122 videotapes were reviewed and rated. Two randomly selected raters evaluated each tape on the 22-item Red Wing Global Scale developed for this evaluation. The primary components of the sessions evaluated by the rating scale involved (1) the adherence of the facilitators to the treatment model, (2) the skill level of the facilitators, and (3) the contribution of the residents to the group processes. Following training, the raters began rating the videotapes in a progression of three rounds (each round consisting of a month) conducted in June, August, and October of 1999.